2022
DOI: 10.1073/pnas.2205564119
|View full text |Cite
|
Sign up to set email alerts
|

Concerted evolution of metabolic rate, economics of mating, ecology, and pace of life across seed beetles

Abstract: Male–female coevolution has taken different paths among closely related species, but our understanding of the factors that govern its direction is limited. While it is clear that ecological factors, life history, and the economics of reproduction are connected, the divergent links are often obscure. We propose that a complete understanding requires the conceptual integration of metabolic phenotypes. Metabolic rate, a nexus of life history evolution, is constrained by ecological factors and may exert important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 112 publications
2
14
0
Order By: Relevance
“…The patterns therefore point to a more direct role of the divergent life history regimes. Reduced sexual dimorphism in physiology (metabolic rate) is associated with adaptation to slower pace of life and longer lifespan across seed beetles ( Arnqvist et al 2022 ), echoing the gene expression divergence we observed in a micro-evolutionary scale.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The patterns therefore point to a more direct role of the divergent life history regimes. Reduced sexual dimorphism in physiology (metabolic rate) is associated with adaptation to slower pace of life and longer lifespan across seed beetles ( Arnqvist et al 2022 ), echoing the gene expression divergence we observed in a micro-evolutionary scale.…”
Section: Discussionmentioning
confidence: 58%
“…The temporal window for multiple mating is restricted in E lines (due to a female refractory period of 2 days in this species; Šešlija et al 2009 ). In addition, L females have evolved a higher remating rate ( Šešlija et al 2009 ), likely to extract water and nutrients from male ejaculates to extend their lifespan ( Arnqvist et al 2022 ). Consequently, E males have evolved under relaxed sperm competition compared with the L males, whereas selection on females from mating interactions would also differ between the regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Resource availability is a limiting factor for many adult lizards in arid and semi-arid environments (Bradshaw, 1997;Congdon, 1989;Kearney & Porter, 2004) occupied by P. vitticeps (Greer, 1989). Resource competition in these systems has been shown to drive selection towards lower metabolic rates when resources are scarce and vice versa when resources are high (Arnqvist et al, 2022;Mueller & Diamond, 2001). The unpredictable resource pulses (high rainfall events/high productivity vs. drought/low productivity) of this region shape demographic processes for other species (Kwok et al, 2016;Letnic & Dickman, 2010;Noy-Meir, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Suites of correlated behavioural traits are also sometimes incorporated into this framework (Réale et al, 2010). Ecological factors clearly have a central role in POL evolution (Dammhahn et al, 2018) and environmental conditions and suites of LH traits often covary across species in many groups (Stearns, 1983): species experiencing more frequent or severe resource limitation tend to show a slower POL compared to species living in environments where resource competition is less intense (Arnqvist et al, 2022).…”
Section: Figurementioning
confidence: 99%